Study of Passivity-Based Decoupling Control of T-NPC PV Grid-Connected Inverter - Wang, Jiuhe; Mu, Xiaobin; Li, Qing-Kui (IEEE transactions on industrial electronics (1982), 2017)
For the purpose of improving the performances of T-type neutral point clamped (T-NPC) photovoltaic (PV) grid-connected inverter under large grid, a passivity-based decoupling control scheme is proposed in this paper. First, the Euler-Lagrange (EL) mathematical model of a T-NPC PV grid-connected inverter with an LC filter is built based on the power circuit and operating principles. Second, with this EL mathematical model and passivity of the inverter, the passivity-based controller is designed by the damping injecting method. Third, by adopting a proportional integral regulator to directly control direct current (dc) voltage, together with passivity-based indirect control, better performances of the dc voltage control can be further obtained. With the proposed passivity-based controller, the PV grid-connected inverter can achieve both dynamic current decoupling under the synchronous rotating dq coordinate and dc side voltage dynamic decoupling, which can improve the quality of the current connected into the power grid. The passivity-based PV grid-connected inverter is with strong robustness against parameters perturbations of resistors and attenuating the influence of delay in the inverter. Moreover, the passivity-based decoupling control scheme proposed in this paper for the T-NPC PV grid-connected inverter has a simple structure, and is easily debugged and realized in engineering. Experimental results under 10-kW prototype show that the proposed control scheme is effective.